ENHANCING ACCURACY AND CONSISTENCY IN TECHNICAL TERMINOLOGY OF TRANSPORTATION: A COMPREHENSIVE APPROACH - Todjidinova Umida Urinboy qizi (Western European Studies, 2024)
This article proposes a comprehensive approach to enhancing the accuracy and consistency of technical terminology translation in the transportation domain, addressing the critical need for effective cross-cultural communication. Drawing upon linguistic theories, computational tools, and domain expertise, our framework integrates machine translation techniques, terminology management systems, and human validation processes. Through a systematic analysis of linguistic challenges and domain-specific complexities within transportation, we present a structured methodology aimed at bridging linguistic gaps while preserving the integrity and specificity of technical terminology. This research contributes to advancing the field of translation studies in transportation, offering practical solutions for professionals and researchers involved in global transportation projects and initiatives
Keywords: terminology; transportation; multilingual; machine translation